Living in Exile: the Experience of Philosophy: Origin, Departure and Development (Balthazar, 2025)
The purpose of this article is to examine the exile of philosophy’s original, more poetic dimension. The central thesis is that philosophy, which was born from poetic roots, has gradually distanced itself from them, forgetting this foundational aspect and embracing only its scientific, methodical, and systematic form as legitimate. This work will therefore explore the reasons behind the marginalization of poetic philosophy and argue for its recovery.